Hypoglycemic potentials of methanolic extracts of selected plant foods in alloxanized mice (2003)
Crude methanolic extracts of five selected edible plant foods were tested for hy poglycemic activity in alloxanized mice. Fasting blood sugar levels were reduced significantly at differing rates. The order of their antidiabetic activity were H. sabdariffa, A. occidentalis, S. americanum, V. amygdalina, G. latifolium, H. sabdariffa, A. occidentalis and S. americanum, utilized at a dose of 100 mg/kg, had similar activity as chlorpropamide (5 mg/kg), which was used as a reference standard, in that they reduced blood sugar levels in mice below the initial values.